Induced abortions in women with systemic lupus erythematosus. (March 2021) - Venne, Karel; Scott, Susan; Bernatsky, Sasha; Vinet, Evelyne
Objectives: To determine the rates of induced abortions in women with systemic lupus erythematosus (SLE) compared to women from the general population and assess disease-related predictors of induced abortion in women with SLE. Methods: We identified women with SLE (15-45 years) and determined the number of induced abortions, using Quebec's administrative databases. We calculated the standardized incidence ratio (SIR) using general population rates. We also performed a nested-case control analysis to investigate predictors of induced abortions in SLE women (such as teratogenic immunosuppressive and corticosteroid exposures). Results: Among 2508 women with SLE, we observed 293 induced abortions [incidence rate of 17.1 induced abortions per 1000 person-years (95% CI 15.2, 19.2)]. There was no clear difference in the number of induced abortions among women with SLE versus women from the general population (SIR 1.10; 95% CI 0.98, 1.24). In the multivariable analysis, we did not observe higher rates of induced abortions among women exposed to teratogenic immunosuppressives [rate ratio (RR) 0.37; 95% CI 0.13, 1.07] or using corticosteroids (RR 0.67; 95% CI 0.39, 1.16). Conclusion: Our findings suggest that women with SLE have a similar rate of induced abortions as compared to the general population. This raises some concerns as unplanned pregnancies in SLE women can lead to adverse maternal and fetal outcomes. Our results should prompt further research on family planning counselling in women with SLE.